2020
DOI: 10.1111/jocn.15562
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with return to work following myocardial infarction: A systematic review of observational studies

Abstract: Objectives To identify and critically synthesise literature on return to work of patients following a myocardial infarction and to identify factors that are associated with this. Background Understanding when patients return to work after myocardial infarction and what factors are associated with this may be helpful in designing person‐centred treatment plans to facilitate patients' rehabilitation and return to work. Design A narrative systematic review. Review methods Six databases, MEDLINE, CINAHL, Academic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 45 publications
2
15
1
Order By: Relevance
“…RTW prevalence estimates varied from 47.3% before three months, 88.0% at 3–6 months, 77% at 6–12 month, to 80% after 12 months. In their systematic review without meta-analysis, Sun et al reported that RTW occurred in 21.5% to 62.5% of the participants within three months which agrees with the expected prevalences observed in our meta-analyses (PI [26.6; 68.4]) 65 . They also suggested that 55.9% to 90% of the participants RTW within 6 to 12 months while our estimations were wider (expected prevalences between 20.2 and 100%).…”
Section: Discussionsupporting
confidence: 91%
“…RTW prevalence estimates varied from 47.3% before three months, 88.0% at 3–6 months, 77% at 6–12 month, to 80% after 12 months. In their systematic review without meta-analysis, Sun et al reported that RTW occurred in 21.5% to 62.5% of the participants within three months which agrees with the expected prevalences observed in our meta-analyses (PI [26.6; 68.4]) 65 . They also suggested that 55.9% to 90% of the participants RTW within 6 to 12 months while our estimations were wider (expected prevalences between 20.2 and 100%).…”
Section: Discussionsupporting
confidence: 91%
“…Studies from the US found that married people with greater physical health and no history of CHD and hypertension were more likely to RTW at 12 months post-MI [10], whereas hospital readmissions, smoking, and hypertension inhibited work resumption during this time [9]. A systematic review demonstrated demographic, behavioral, clinical, and psychosocial factors significantly related to a work resumption post-MI, including gender, age, educational level, work type, duration of hospitalization, comorbidities, complications, mental health, and self-evaluated general health [24]. However, no study has focused on the Korean population regarding this topic.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…To answer research question 2, demographic, behavioral, and clinical variables were chosen based on the findings of a systemic review of factors related to RTW after MI [24].…”
Section: Demographic Behavioral and Clinical Datamentioning
confidence: 99%
See 2 more Smart Citations